2020
DOI: 10.3390/plants9121628
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Regions Associated with the Control of Flowering Time in Durum Wheat

Abstract: Flowering time is a critical stage for crop development as it regulates the ability of plants to adapt to an environment. To understand the genetic control of flowering time, a genome-wide association study (GWAS) was conducted to identify the genomic regions associated with the control of this trait in durum wheat (Triticum durum Desf.). A total of 96 landraces and 288 modern lines were evaluated for days to heading, growing degree days, and accumulated day length at flowering across 13 environments spread ac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 67 publications
1
15
0
Order By: Relevance
“…Interestingly, the QTLs identi ed using dNAM for PH on chromosomes 1B, 2B, 4A, 5B, 6A, 6B, 7A, and 7B were also reported in previous studies (Milner et al 2016). Also, the most signi cant QTL associated with DTF in this study is aligned with the recently reported owering genes ppd-1B, Vrn1, and Vrn2, which were previously mapped to chromosomes 2A, 2B, and 5A, respectively (Gupta et al 2020). In addition to the previously reported QTLs for PH and DTF, six novel QTLs controlling DTF and six for PH were detected using the dNAM population developed in our study.…”
Section: Durum Nam Population Development and Diversitysupporting
confidence: 87%
“…Interestingly, the QTLs identi ed using dNAM for PH on chromosomes 1B, 2B, 4A, 5B, 6A, 6B, 7A, and 7B were also reported in previous studies (Milner et al 2016). Also, the most signi cant QTL associated with DTF in this study is aligned with the recently reported owering genes ppd-1B, Vrn1, and Vrn2, which were previously mapped to chromosomes 2A, 2B, and 5A, respectively (Gupta et al 2020). In addition to the previously reported QTLs for PH and DTF, six novel QTLs controlling DTF and six for PH were detected using the dNAM population developed in our study.…”
Section: Durum Nam Population Development and Diversitysupporting
confidence: 87%
“…Distelfeld et al ( 2009 ) reported that Vrn-1 genes regulate the transition from vegetative to reproductive phase in response to temperature and thus determine the spring and winter growth habit. Therefore, evaluation of DH in the MDL population revealed the three genomic loci reported to control flowering time in wheat (Pánková et al 2008 ; Kobayashi et al 2016 ; Gupta et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…GWAS was also performed for the heat susceptibility index (HSI) for the 'discovery panel'. The signi cant MTAs identi ed were merged into 36 signi cant QTL spread across all durum wheat chromosomes (Table S3), after removing any QTL with associated with the control of phenology (Gupta et al 2020). Comparing these QTL to those identi ed in the heat stress study by El Hassouni et al (2019) run using a subset of the 'discovery panel', con rmed 17 QTLs as cross-validated.…”
Section: Marker-trait Associations (Mtas) Of the 'Discovery' And 'Inv...mentioning
confidence: 99%
“…Pearson's critical value (Pearson 1895) for correlation was squared to obtain a critical r 2 = 0.032 at P < 0.05 for both panels, which was used as the threshold to determine QTL that explained a signi cant part of the phenotypic variance. To further remove the effect of phenology from QTL discovery, any QTL overlapping with a signi cant MTA identi ed for DTH (see Gupta et al 2020) was removed from all downstream considerations. Haplotype analysis was conducted on the 'discovery panel' to de ne which QTL were additive in nature.…”
Section: Genome-wide Association Study (Gwas)mentioning
confidence: 99%